Real-world solutions for developing high-quality PHP frameworks and applications - Bergmann, Sebastian
Packed with in-depth information and step-by-step guidance, this book escorts you through the process of creating, maintaining and extending sustainable software of high quality with PHP. World-renowned PHP experts present real-world case studies for developing high-quality applications and frameworks in PHP that can easily be adapted to changing business requirements. . They offer different approaches to solving typical development and quality assurance problems that every developer needs to know and master. Details the process for creating high-quality PHP frameworks and applications that can easily be adapted to changing business requirements Covers the planning, execution, and automation of tests for the different layers and tiers of a Web application Demonstrates how to establish a successful development process Shares real-world case studies from well-known companies and their PHP experts